Powering the future: the latest breakthrough in wireless charging for electric vehicles - Fry, Matthew; Muhammad Usama Islam, Muhammad Usama Islam; Syed Zahurul Islam, Syed Zahurul Islam; Jasim Uddin, Jasim Uddin (2024)
Recently, the Electric Vehicle (EV) market has experienced significant growth and is projected to expand exponentially with the advancement of technology. Major industries are increasingly adopting the concept of producing hybrid or fully electric cars, resulting in electric vehicles becoming a common sight in today’s era. This research examines the potential of wireless power transfer systems as an alternative method of charging electric automobiles. Despite the widespread use of traditional plug-in charging, wireless charging proves to be more effective and convenient. The study evaluates various approaches to integrating wireless charging into an electric vehicle prototype, represented by a remote control car. It also explores the background and advancements of wireless charging technology. By optimising the design of the transmitter and receiver, based on circuits used for mobile phone chargers, the necessary power (5V, 2A) is provided to the remote-controlled car. Voltage regulators are utilized to manage the output voltage of the receiver circuit during simulations, which assess the circuit’s performance under different conditions. The results suggest that wireless charging could serve as a practical and environmentally friendly alternative to conventional charging methods.